Determination of the optimal location of a 2-DoF manipulator for minimal energy consumption during a predefined task - Kopmaz, Mehmet Beşir; Bütün, İsmail; Bursa Teknik Üniversitesi Mekatronik Mühendisliği Ana Bilim Dalı; Fen Bilimleri Enstitüsü (Bursa, 2016)
In the past several decades, robot manipulators have been indispensable part of serial production due to their huge contribution to the efficient, accurate and rapid manufacturing. On the other hand, it is a well-known fact that the efficient use of energy has been the main challenge from the first industrial revolution to date due to limited energy resources and their geo-political locations on the world. Considering that one of the largest consumers of energy is manufacturing industry, the importance of time- and energy-optimal usage of production machinery, specifically in this context can be well figured out. For this reason, in the field of robotics, an interesting research area has emerged under the headline of trajectory planning subject to different constraints among which time-optimal, energy-optimal or smooth (jerk- and impact-free) path tracking can be mentioned at first glance. This thesis is concerned with minimizing the energy consumption for a given task and trajectory. The present study differs from the previous work in that energy consumption is minimized by obtaining an appropriate location for the manipulator with respect to the trajectory fixed in the world coordinates. In this work, trajectories are assumed to be straight-lines. Besides, two different motion programs known with their smooth kinematic characteristics are tested, which are the cycloidal and the 3-4-5 polynomial motion programs. Numerical results obviously demonstrate that obtaining an optimal location for the manipulator regarding the use of minimal energy is possible, and the 3-4-5 polynomial motion program provides less energy consumption levels.
Tez (Yüksek Lisans)-Bursa Teknik Üniversitesi Fen Bilimleri Enstitüsü, 2016
Kaynakça var.
Keywords: Minimum energy